Anti-obesity Effect of Dextromethorphan in High Fat Diet Induced Obesity in Rats (KSV Journal of Pharmacy and Health Sciences, 2024)
Obesity is associated with significant comorbidities. Treatment options for obesity include only few drugs. Several hormones and receptors play key role in pathogenesis of obesity like NMDA, PPAR-gamma, leptin, pro-opiomelanocortin (POMC) and others. To check  anti-obesity effect of Dextromethorphan (DXM) in high fat diet (HFD) induced obesity. Male Wistar albino rats (BW- 250-350 grams) were divided into 5 groups. Group 1 (Normal control) was fed with standard pellets. All the remaining groups were fed with High fat diet (HFD) to induce obesity. Group 2 served as HFD control. Group 3 (standard), group 4 (DXM-P) and group 5 (DXM-T) received orlistat (10 mg/kg, day 49 to 84), dextromethorphan (DXM) (15 mg/kg, day 0 to 84) and DXM (15 mg/kg, day 49 to 84) respectively. All the drugs were administered orally. Food intake (daily), water intake (daily) and body weight (weekly) were measured. Serum cholesterol (TC), Serum triglyceride (TG), HDL and LDL; OGTT, BMI, white adipose tissue (WAT) mass were measured.  No significant difference was observed in food intake, BMI, TC, LDL and HDL between disease and treatment groups. BMI was significantly increased in HFD group and decreased in orlistat and DXM-P group. WAT mass and blood glucose were significantly decreased in all treatment groups as compared to HFD control. Administration of dextromethorphan in both the groups improved body weight, BMI (only DEX-P), WAT mass, glucose tolerance and serum TG. Dextromethorphan can be further studied for further development in treatment of obesity.